Step-up to medicine - Agabegi, Steven S.; Agabegi, Elizabeth D. (Step up series., 2008)
This book is a primary review tool to prepare students for both the internal medicine clerkship and the end-rotation NBME shelf examination. This logical alternative to several limited-focus books blends a bullet-outline format students prefer in a review book with comprehensive paragraphs, as needed, for optimal preparation.